Climate Change Mitigation and Adaptation Policies in Nigeria - Daniel Mevayerore Igbini; Veronica Uchechukwu Ikenga; Jeremiah Avwenaghogho Oharisi (Journal of Social Science and Humanities, 2026)
Climate change has become one of the most pressing environmental and socio-economic challenges globally, and Nigeria is particularly vulnerable due to its reliance on agriculture, energy production, and natural resources. This study examined the policies and strategies adopted by the Nigerian government to mitigate and adapt to the impacts of climate change, highlighting their effectiveness, challenges, and implications for sustainable development. Employing a historical research design, the study analyzed secondary data from government policy documents, environmental reports, academic literature, and international climate agreements to trace the evolution of climate policies in Nigeria over time. The study was anchored on the Sustainable Development Theory, which emphasizes the integration of environmental, social, and economic considerations in policy planning to ensure the long-term well-being of society. Findings indicate that Nigeria has developed a range of mitigation and adaptation policies, including the National Climate Change Policy, the National Adaptation Strategy and Plan of Action (NASPA), and participation in the Paris Agreement. These policies have led to some progress in renewable energy development, afforestation programs, and community-based adaptation projects. However, challenges such as weak institutional capacity, inadequate funding, poor enforcement mechanisms, and limited public awareness continue to undermine policy effectiveness. The study concluded that Nigeria’s climate policies are ambitious but constrained by systemic and structural weaknesses. To move from policy formulation to measurable outcomes, the country must strengthen governance, boost domestic financing, and prioritize inclusive, community-driven approaches. It is recommended, among others, that the government should strengthen institutional capacity and policy enforcement by improving coordination among ministries, agencies, and state governments, while building technical expertise and establishing robust monitoring systems to ensure accountability.